Epigenetically regulated Fibronectin leucine rich transmembrane protein 2 (FLRT2) shows tumor suppressor activity in breast cancer cells - Bae, Hansol (Sci Rep, 2017)
To identify dysregulated genes by abnormal methylation and expression in breast cancer, we genome-wide analyzed methylation and expression microarray data from the Gene Expression Omnibus and the Cancer Genome Atlas database. One of the genes screened in silico, FLRT2, showed hypermethylation and downregulation in the cancer dataset and the association was verified both in cultured cell lines and cancer patients’ tissue. To investigate the role of FLRT2 in breast cancer, its expression was knocked down and upregulated in mammary cell lines, and the effect was examined through three levels of approach: pathway analysis; cell activities such as proliferation, colony formation, migration, and adhesion; target gene expression. The top pathway was “Cellular growth and proliferation”, or “Cancer”-related function, with the majority of the genes deregulated in a direction pointing to FLRT2 as a potential tumor suppressor. Concordantly, downregulation of FLRT2 increased cell proliferation and cell migration, while overexpression of FLRT2 had the opposite effect. Notably, cell adhesion was significantly decreased by FLRT2 in the collagen I-coated plate. Taken together, our results provide insights into the role of FLRT2 as a novel tumor suppressor in the breast, which is inactivated by hypermethylation during tumor development.